Sertifikasi dan Paradoks Legitimasi Profesionalitas Jurnalis di Indonesia - Nurlatifah, Mufti (Jurnal Riset Komunikasi (JURKOM), 2025)
Journalist certification legitimizes Indonesia’s journalists’ professionalism in producing, managing, and disseminating information, including serving the public interest. According, to Indonesia’s Journalist Competency Test (UKW), journalists can be determined based on their competence level, such as young journalists, middle journalists, and senior journalists. Those three levels also dictate journalist into their position and function at media institutions. This condition presents a confluence of opportunities and challenges in Indonesian journalism professional practice. Journalists certification, on the one hand, validates the professionalism of journalists in the performance of their jobs and sets them apart from other information producers. But, on the other hand, normative measurement through certification mechanisms also promotes strict standardization which violates media freedom vigor for journalism. Paradoxically, the energy to raise journalist standards is unequal to the other areas of professional journalism, like attempts to raise the standard of quality content journalism itself and being professional journalists ethically, remain unaffected. This study elaborates on Indonesia’s condition in descriptive and qualitative analysis of journalist certification data from the Indonesia Press Council. Although the quantification of Indonesian journalists is still a delightful success on paper, it raises questions about the caliber of journalists and journalism practices in Indonesia.